The Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST) Performance in Elite Team Handball Players Playing with Shoulder Pain, Previous Pain, or No Pain - Tina Piil Torabi; Jesper Bencke; Roland van den Tillaar (International Journal of Sports Physical Therapy)
# Background